HR Policy Development for a Heating, Ventilation and Air-Conditioning Contractor in Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This industrial and development corporation in Quezon City, established in 1978, is the leading contractor in heating, ventilation and air-conditioning in the Philippines. It has around 2,802 employees where 700 are regular and 2,102 are project based employees. The researcher wants to review and enhance the company’s current policies in accordance with the law of the land and best practices of other companies. The researchers used qualitative method of research. Face-to-face interviews with HR officers and questionnaires were used to gather data. The researchers also gathered data from different construction companies as a basis for comparison. The researchers also rendered 400 hours of internship in the company which allowed them to observe common practices and procedures. Upon review of the company’s policies, the researchers found out that the company has 33 current HR policies that includes: Government Mandated Benefits, Health and Safety Guidelines, Dress Code, Drug-Free Workplace Policy and Code of Discipline. The researchers proposed enhancement on the records system and employee job description and development of 10 policies and programs, namely: Anti –Nepotism; HMO; Birthday Leave; Performance Evaluation Management; Corporate Wellness Program; Seminar on Work Values; Transportation Allowance; Lateral Transfer; 360 Feedback and Open Door Policy. Policies proposed in this research paper aim to help the company achieve better workplace results in terms of rules, regulations and policies.
Keywords: policy development, procedures, industrial and development company